Recipient Venule Selection and Anastomosis Configuration for Lymphaticovenular Anastomosis in Extremity Lymphedema: Algorithm Based on 1,000 Lymphaticovenular Anastomosis - Bianchi, Alessandro; Salgarello, Marzia; Hayashi, Akitatsu; Yang, Johnson C.-S.; Visconti, Giuseppe (Journal of Reconstructive Microsurgery, 2021)
Background The lymphaticovenular anastomosis (LVA) has three components, lymphatics, venules, and anastomosis, and all of them influence the anastomotic pressure gradient. Although it has been demonstrated that venule flow dynamics has an independent impact on the outcomes regardless the degeneration status of lymphatic vessels, recipient venules (RV) have been mainly neglected in literature.Methods From January 2016 to February 2020, 232 nonconsecutive patients affected by extremity lymphedema underwent LVA, for a total of 1,000 LVAs. Only patients with normal-to-ectasic lymphatic collectors were included to focus the evaluation on the RV only. The preoperative collected data included the location, diameter, and continence of the selected venules, the expected number, the anastomoses configuration, and their flow dynamics according to BSO classification.Results The 232 patients included 117 upper limb lymphedema (ULL) and 115 lower limb lymphedema (LLL). The average size of RV was 0.81 ± 0.32 mm in end-to-end (E-E), 114 ± 0.17 mm in end-to-side (E-S), 0.39 ± 0.22 mm in side-to-end (S-E), and 0.76 ± 0.38 mm in side-to-side (S-S) anastomoses. According to the BSO classification, on a total of 732 RV, 105(14%) were backflow venules, 136 (19%) were slack, and 491 (67%) were outlet venules. Also, 824 (82%) were E-E, 107 (11%) were E-S, 51 (5%) were S-E, and 18 (2%) were S-S anastomoses.Conclusion Based on 1,000 LVAs with similar lymphatic characteristics, we propose our algorithm that may aid the lymphatic microsurgeon in the selection of RV and the consequent anastomosis configuration, in order of obtain the best flow dynamic through the LVA. This therapeutic study reflects level of evidence IV.
Keywords: LVB; LVA; supermicrosurgery